Fixed Trajectories: Race, Schooling, and Graduation from a Southern Ontario University - James, Carl E.; Parekh, Gillian (Canadian Journal of Higher Education, 2021)
According to Statistics Canada, during this decade (2019–2028) about 75% of new jobs will require a post-secondary education (Government of Canada, 2017). This study explores a unique dataset that follows students (n = 11,417) from a large urban school district to a local university in Southern Ontario. Using both descriptive statistics and a binary logistic regression and a framework of categorical inequality (Domina et al., 2017), we examine the academic trajectories of students—particularly of Black students. Findings show that, compared to their peers, neither high school nor university programs provide Black students with the kinds of educational experiences needed for university graduation and academic success that would enable them to realize their fullest social and economic potentials.